Information asymmetries, uncertainties and cleanup delays at superfund sites - Gordon Clyde Rausser; Leo K. Simon; Jinhua Zhao (Fondazione Eni Enrico Mattei (FEEM), 1997)
Superfund cleanup has been extremely slow. Traditional analysis has centred around reducing the heavy negotiation and litigation to expedite the cleanup process. This paper investigates other factors which provide possible incentives for the PRPs to delay the cleanup, namely discounting, risk aversion, and compensation for off-site damage. Liability share is found to play an essential role in PRP's incentives to delay. Commonly adopted EPA strategies, such as negotiating with PRP steering committees and buying out de minimis PRPs, may provide incentives to delay the cleanup. The paper also designs a Bayesian mechanism for information extraction, and finds that the lump sum transfer mechanism is not always efficient.
Keywords: D82; Q28; 330; Environmental economics; Superfund; CERCLA; Potentially responsible parties (PRPs); Strategic information transmission; Strategic delay; Environmental remediation; Cleanup